Explanatory Remarks on Maslow's Theory of Motivation - Moses Adeleke Adeoye (Indonesian Journal of Multidiciplinary Research, 2022)
An accessible explanation of Maslow's Theory of Motivation is provided in this article. For readers who want to use the article for basic knowledge, fundamental ideas are given. The review is meant to provide senior and graduate students studying business management, educational psychology, and educational management with a self-study approach. It might also be used in academia and business as a textbook or reference.